Disruption of Gut Microbiota and Associated Fecal Metabolites in Collagen-Induced Arthritis Mice During the Early Stage - Wu D; Yin M; Cao D; Zhang X; Zhu Y; Wei Y; Li Y; Wen C; Zhou J (Journal of Inflammation Research)
Dehong Wu,1,* Mengdi Yin,2,* Dandan Cao,2,* Xiafeng Zhang,2 Yichun Zhu,2 Ying Wei,2 Yiling Li,2 Chengping Wen,2 Jia Zhou2 1Department of Rheumatology, The Second Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310005, People’s Republic of China; 2Institute of Basic Research in Clinical Medicine, College of Basic Medical Sciences, Zhejiang Chinese Medical University, Hangzhou, 310053, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jia Zhou; Chengping Wen, Email zhoujia@zcmu.edu.cn; chengpw2010@126.comBackground: Rheumatoid arthritis (RA) is a chronic autoimmune disease and increasing evidence suggests that disturbances in the composition and function of gut microbiota are potentially implicated in the progression of RA. Further revealing the microbiota and related metabolic disorders in the preclinical stage of RA (pre-RA) is of great significance for exploration of disease mechanisms.Methods: DBA/1 mice were injected with type II collagen on days 0 and 21 to establish collagen-induced arthritis (CIA) mouse model. Footpad thickness, serum autoantibodies, and joint histopathology were used to assess the progression of RA. A combination of 16S rRNA sequencing, untargeted metabolomics and targeted short-chain fatty acids (SCFAs) analysis were employed to comprehensively investigate the alterations of gut microbiota and fecal metabolites in CIA during the pre-RA stage.Results: 20 days after the initial collagen immunization, CIA mice showed immune responses without joint symptoms, alongside gut microbiota disruption. Alterations were observed in 20 microbial taxa, including Oscillospira, Bifidobacterium, Ruminococcus, Allobaculum, Alistipes, Lactobacillus, and Candidatus_Arthromitus, etc. Untargeted and targeted metabolomics identified 33 altered fecal metabolites, mainly including sugars and their derivatives, amino acids, long-chain fatty acids and SCFAs, etc. Correlation analysis showed significant correlations between specific gut microbial abundances and fecal metabolite levels. Especially, SCFAs were strongly associated with Bifidobacterium, Alistipes, Ruminococcus, Anaerotruncus, and Allobaculum.Conclusion: These findings suggest that collagen immunization leads to disruption of gut microbiome and induces changes of fecal metabolites in mice, which may play a key role in early development of RA in CIA mice.Keywords: gut microbiota, fecal metabolites, short-chain fatty acids, preclinical stage, collagen-induced arthritis